An analysis of the implications of taxation on equity in relation to national development - Maulana, Ayang Fristia; Apiati, Siti Nurfadilah; Arofah, Laila; Aditiya, Arya; Solihin, Muhammad (Journal of Law Science, 2024)
Taxation is a very important instrument for a government in collecting funds to finance various development programs, the nature of this tax is mandatory. Apart from that, this tax system can be designed as well as possible, by making it a tool to achieve social and economic justice, through income redistribution. National development is taxation carried out effectively with the aim of reducing economic imbalances between regions and increasing investment in social services. Excessive or unfair taxation can discourage investment and can destroy incentives to work. This increase in taxes on development can be done to increase the number of buildings owned by Indonesia. With tax reform that focuses on justice and efficiency, this can support a more sustainable national development.